Regulation of HvASN1 expression by bZIP transcription factors during barley embryo development and germination - Estefanía Contreras; Rosario Alonso; Elena Pastor-Mora; Mar G. Ceballos; Jesús Vicente-Carbajosa; Raquel Iglesias-Fernández (Planta, 2025)
Main conclusion Our findings provide new insights into the molecular mechanisms that regulate N metabolism in barley and potentially other cereal crops, offering valuable perspectives for enhancing N use efficiency in agricultural practices. Abstract Efficient nitrogen (N) utilization is essential for plant growth, especially during seed development and germination. In barley ( Hordeum vulgare ), the asparagine synthetase gene HvASN1 is essential for nitrogen transport and storage, synthesizing asparagine, a key molecule in N recycling. The phylogenetic analysis indicates that HvASN1 clusters with Arabidopsis AtASN1 and shares high similarity with HvASN2, suggesting a conserved role in N metabolism. A detailed characterization of a ~ 500 bp HvASN1 promoter region revealed a conserved GCN-like cis -element. Transient expression assays in Nicotiana benthamiana demonstrated that the wild-type promoter significantly increases luciferase activity under dark conditions, whereas mutation of the GCN-like element reduces this activity, highlighting its role in light-responsive gene regulation. Further investigation identified the bZIP transcription factor HvbZIP53 as an activator of the HvASN1 promoter through binding to the GCN-like element. This activation is finely tuned by sucrose via a conserved upstream open reading frame (uORF) in HvbZIP53’s 5′ UTR, which mediates sucrose-induced repression of translation. Additionally, yeast two-hybrid assays and transient expression studies in Arabidopsis provided evidence that HvbZIP53 physically interacts with HvBLZ1, a C group bZIP factor, resulting in a synergistic enhancement of HvASN1 expression. The spatial and temporal expression analyses further revealed that HvASN1 , HvbZIP53 , and HvBLZ1 are co-expressed in key seed tissues during development and germination. These findings indicate a complex regulatory network integrating environmental and metabolic signals to modulate N metabolism in barley, with implications for improving N use efficiency in cereal crops.